The diatom world - Seckbach, Joseph; Kociolek, Patrick; SpringerLink (Online service). (Dordrecht Springer Netherlands, 2011)
Diatoms are fascinating algae, whose relevance today is greater than perhaps ever before. They are important players in a wide range of ecosystems, freshwater, brackish and marine. They are also being investigated as a source of renewable biofuels. Because the literature on diatoms is published in a diverse set of journals under many different disciplines, it is hard for people to track down the diverse array of cutting edge research results on the group. The Diatom World brings together many of the experts in the world of diatom research, who summarize important topics on diatom classification, biology, genomics research, and a broad spectrum of ecological studies, and present new data in these areas. The topics address age-old questions, and explore new and emerging areas of research. In this combination of persistent questions, and new horizons, it is clear that the diatoms remain as fascinating and intriguing today as they were when Von Leeuwenhoek first spied them over 300 years ago. We suspect interest in this group will grow in the years to come, as many new fields emerge around their biology, geological record, incredible morphologies and ecological breadth.
Foreword; - Opening -- Collecting, Cleaning, Mounting and Photographing Diatoms -- PART 1: TAXONOMY, SYSTEMATICS AND PHYLOGENY -- Morphology: Cell Wall, Cytology, Ultrastructural And Morphogenetic Studies -- An Overview Of Diatom Classification With Some Prospects For The Future -- A Review of the Evolution of The Diatoms From the Origin of the Lineage to Their Populations -- Status of the Pursuit of the Diatom Phylogeny: Are Traditional Views and New Molecular Paradigms Really that Different? -- PART 2: DIATOM BIOLOGY -- Size and Sex -- Classical Breeding in Diatoms: Scientific Background And Practical Perspectives -- Epizoic And Epiphytic Diatoms.-Diatom Viruses -- Diatom Biofilms -- Possible Buckling Phenomena In Diatom Morphogenisis -- Diatom Frustules: Physical, Optical, and Biotechnological Applications -- PART 3: FRESHWATER ECOLOGY -- Importance of Scale in Understanding the Natural History Of Diatom Communities -- Patterns of Diatom Distribution In Relation to Salinity -- Diatoms From Hot Springs From Kuril And Sakhalin Islands (Far East, Russia) -- Living On the pH Edge: Diatom Assemblages of Low pH Lakes In Western Pomerania (NW Poland) -- The Diatom Algae of Lake Kinneret, Israel -- Rheophile Apennine Diatoms and Their Use as Bioindicators Of Water Quality -- PART 4: MARINE ECOLOGY -- Ecophysiological Performance of Benthic Diatoms from Arctic Waters -- Diatoms as Endosymbionts -- Marine Planktonic Diatoms, Including Potentially Toxic Species -- Toxic Diatom Pseudo-Nitzschia And Its Primary Consumers (Vectors) -- PART 5: SUMMARY -- Summary.-.
Keywords: Diatoms; Electronic books